2019
DOI: 10.3906/tar-1802-106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulators on the plant height and quantitative properties of Narcissus tazetta

Abstract: The effects of flurprimidol, paclobutrazol, and ethephon treatment as soil drench on plant height and quantitative and other properties of native narcissus (Narcissus tazetta L.) plants grown in pots were investigated. When the plants were 7-10 cm tall, flurprimidol and paclobutrazol at 0, 1, and 2 mg/pot and ethephon at 0, 37.5, and 75 mg/pot were applied as soil drenches. The effects of plant growth retardant treatments on plant height, leaf length, time of flowering, number of flowers, and flower life were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…These phytohormones, at very low doses, regulate various physiological functions at all developmental stages of plants, such as germination, rooting, flowering, dormancy, and so on. Therefore, as endogenous signals, such compounds act both temporally and spatially (Demir & Celikel, 2019; Gundesli et al, 2019; Sajjad et al, 2017). Melatonin is a bio‐molecule which is widely studied, with the molecular name of N ‐acetyl‐5‐methoxytryptamine.…”
Section: Introductionmentioning
confidence: 99%
“…These phytohormones, at very low doses, regulate various physiological functions at all developmental stages of plants, such as germination, rooting, flowering, dormancy, and so on. Therefore, as endogenous signals, such compounds act both temporally and spatially (Demir & Celikel, 2019; Gundesli et al, 2019; Sajjad et al, 2017). Melatonin is a bio‐molecule which is widely studied, with the molecular name of N ‐acetyl‐5‐methoxytryptamine.…”
Section: Introductionmentioning
confidence: 99%
“…Stem elongation was inhibited in gibberellin-deficient Arabidopsis mutants (Sun and Kamiya, 1994;Chiang et al, 1995), and the gibberellin inhibitor paclobutrazol suppresses growth in a wide range of plant species by decreasing the concentrations of endogenous gibberellins (Tsegaw et al, 2005). Gibberellin inhibitors have been used during production to control the plant height after harvest (Miller, 2012) and in the production of potted bulbous flowers (Demir and Çelikel, 2019). Since the inhibition of extension growth in TDZ-treated roses did not appear to be the result of stimulated ethylene production, we investigated the effects of TDZ on expressions of genes encoding enzymes involved in gibberellin biosynthesis and degradation (catabolism).…”
Section: Discussionmentioning
confidence: 99%
“…The lower light conditions in homes and offices could result in an increase in plant height and a reduction of postharvest quality. To provide compact plants, growers apply plant growth regulators, such as ethylene (released from ethephon) (Çelikel and Demir, 2019), or more commonly, inhibitors of gibberellin biosynthesis (such as flurprimidol, ancymidol, and paclobutrazol) (Miller, 2012;Demir and Çelikel, 2019), to suppress extension growth after production. Our findings that the anti-yellowing effect of TDZ was accompanied by a marked reduction of elongation growth are therefore of considerable practical interest.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to know the growing techniques of indoor plants such as plant height control especially in bulbous flowers (Çelikel, 2015). Plant height may be controlled by physical or chemical methods with plant growth retardants mostly gibberellin inhibitors (Çelikel et al, 2016;Demir and Çelikel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad Nazarudin et al (2007), reported that paclobutrazol treatments caused the control of plant height by decreasing the leaf area and leaf expansion. Demir and Çelikel (2019) used gibberellin inhibitors as soil drench to investigate the plant height control of Narcissus tazetta grown naturally in Black Sea Region of Turkey. However, there is no previous study on bulb soak treatments of inhibitors in this species.…”
Section: Introductionmentioning
confidence: 99%